Mothballed Mount Everest climate observatory could reopen by early next year. (1st November 2018) - Del Bello, Lou
A group that helped create the Nepal Climate Observatory - Pyramid approaches a deal with the Italian funding agency that once bankrolled it. The group that created the Nepal Climate Observatory - Pyramid approaches a deal with the Italian funding agency that once bankrolled it.